Dogmatika, Filsafat Hukum Islam dan Hak Asasi Manusia: Sketsa Agenda Rekonstrran dan Penafsiran Hukum Islam - JM Muslimin (Qur'an and Hadith Academic Society, 2016)
In its formative years, Islamic law develops gradually. Along its development as a concept of reasoning as well as judging, Islamic law is a result of mixed and blended elements: a transcendental and local elements are formulated to be a coherent reference of logics. The article proposes the continuation of the blended tradition. The basic assumption is as long as sharia is able to maintain its adaptability to the newest cultural innovation and create ‘creative dialectics’ as it is shown in its glorious history of human civilization, it will survive as a moral guidelines and legal frame of thought. The article tries further to offer a model of such a creativity, especially with regard to the concept of human rights.